2008
DOI: 10.1007/s10554-008-9306-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and pulmonary arterial hypertension on the different phases of right atrial function

Abstract: To evaluate the effects of age and pulmonary hypertension on phasic right atrial function we measured right atrial volumes at 3 different points in the cardiac cycle in 57 healthy subjects and 33 patients with pulmonary arterial hypertension. Right atrial reservoir function was assessed by systolic filling volume and passive and active emptying by passive and active emptying volume and fraction of total emptying. We compared these phases of right atrial function in 30 healthy subjects <60 and 27 > or = 60 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
34
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 24 publications
12
34
0
2
Order By: Relevance
“…For example, increase in the systolic function of the right atrium has been documented by two-dimensional measurements(13), by Doppler methods (17), and by pulsed tissue Doppler imaging (14). The increased RA EF in PH patients with WHO-FC III seen in the present study is consistent with these prior observations.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…For example, increase in the systolic function of the right atrium has been documented by two-dimensional measurements(13), by Doppler methods (17), and by pulsed tissue Doppler imaging (14). The increased RA EF in PH patients with WHO-FC III seen in the present study is consistent with these prior observations.…”
supporting
confidence: 89%
“…In 2008, an echocardiographic study by Willens et al demonstrated that RA volume was higher in PH patients than in controls (17). RA dilatation in PH was also shown in another echocardiographic report by Cioffi et al (13).…”
mentioning
confidence: 81%
“…These three points in diastole were labeled RAmax (maximum RA volume in the cycle), RAp (RA volume before RA systole), and RAmin (minimum RA volume in the cycle), respectively, as described previously. 12 RA area and volume measurements were made in the apical 4-chamber view with digital calipers, by digitally tracing the RA endocardium (defined as the border between the echocardiographic signal of the RA endocardium [white] and the RV cavity [black]) at the corresponding points in 2 consecutive cardiac cycles (see Fig. 2) and averaging the values.…”
Section: Echocardiographic Techniquesmentioning
confidence: 99%
“…However, data about the interaction of the RV with the right atrium (RA) are sparse. Studies (10,21,28) have been conducted that assessed components of RA function in animals and humans with pulmonary arterial banding or pulmonary hypertension. A study by Hui and coworkers (15) investigated TOF patients with a focus on late atrial active emptying, the so-called atrial kick.…”
mentioning
confidence: 99%